MEASURING DIGITAL PROFICIENCY: A SIMPLE APPROACH USING AN ON-LINE INSTRUMENT - Marques Junior, E.; Oliveira Neto, J. D.; Marques, E. M. R. [UNESP]; GomezChova, L.; LopezMartinez, A.; CandelTorres, I (Iated-int Assoc Technology Education A& Development, 2015)
Digital inclusion has recently become a concern of society and there are many re-sources to promote digital literacy. However, only the access to new technologies and digital literacy are no longer sufficient to deal with the current challenges, as they have also require a high level of Digital Proficiency. Digital Proficiency measures how effectively individuals and organizations deal with digital technol-ogy. Individuals use technology for their own benefit and organizations use it to serve their external customers and employees (internal customers). Technology has influenced every aspect of our lives, from communication, collaboration and learning to information. It allows individuals and organizations to innovate, solve problems, improve productivity, make decisions and even win competitions. There are certification methods that evaluate the individual knowledge and skills associated with the use of Internet and computer. These skills are considered essential for academic learning and a minimum requirement for employment in a typical office environment. These methods evaluate aspects related to the use of hardware, operating systems and software, such as Word and Excel as well as Internet usage. As these certification and evaluation programs are not easily accessible due to costs and location of the tests, we have developed an online tool for the diagnosis of Digital Proficiency by using a case study in which students of a public university are compared with school teachers in Brazil (n = 333).
Keywords: Digital Proficiency; Literacy; Online Survey; Evaluation